The Influence of Entrepreneurship Orientation Motivation Perception of Opportinities on Entrepreneurship Practices at Vocational High School - Yendi, Meizi Syafri; Wahid, Reza Nur; Yessa, Fadilla; Putri, Atika Dwi; Evanita, Susi (The Indonesian Journal of Computer Science, 2023)
This study aims to examine the relationship between entrepreneurial orientation, entrepreneurial motivation, and perceptions of opportunities with entrepreneurship practices of Vacational High School students. The research method used is associative (relationship). This research was conducted on class XII students majoring in Accounting at Vacational High School 3 Padang. The number of samples in this study were 100 respondents. The sampling technique is saturated sampling, because the entire population in this study is used as a respondent. Data collection was obtained from the results of direct and online distribution of questionnaires to students. Data analysis in this study uses multiple linear regression analysis. The results showed that there was a positive and significant relationship between students' entrepreneurial orientation and their entrepreneurial practices. In addition, entrepreneurial motivation also has a positive influence on students' entrepreneurial practices. Perceptions of business opportunities are also positively correlated with students' entrepreneurial practices. This research provides evidence that the development of entrepreneurial orientation, entrepreneurial motivation, and perceptions of opportunities can encourage entrepreneurial practices in Vacational High School students. The results of this study have important implications for education in vocational high schools to strengthen student entrepreneurship learning and development. In addition, this study also underlines the need for attention to these factors in designing effective entrepreneurship programs in schools.